Science, technology and bioethics: a relation of mutual implications - Jiménez Domínguez, Rolando V.; Rojo Asenjo, Onofre (Acta Bioethica, 2008)
This article deals with the subject of values in science and technology from the techno-scientific perspective, providing a philosophical basis for discussion. Various technological advances which affect the lives of people and human relations, are reviewed as well as the possible forms these effects can adopt in the future. Questions which naturally result from these and other technological developments are considered, and a policy of social participation in the big decisions about science and technology is proposed, with emphasis on the importance of spreading a scientific culture in society. Finally, the article considers science and technology as systems not devoid of values, and ponders the implications of this concept for research activities and the formation of human resources in scientific and technical areas.